Morphogenic effect of common solvent in the self-assembly behavior of amphiphilic PEO-b-PLA. (18th March 2021) - Simonutti, R.; Bertani, D.; Marotta, R.; Ferrario, S.; Manzone, D.; Mauri, M.; Gregori, M.; Orlando, A.; Masserini, M.
Abstract: The formation of block copolymer nanoparticles is commonly obtained by switching solvent quality from good solvent for both blocks to a selective solvent for one block. The effect of the selective solvent on particle dimension, shape and inner structure has been analyzed in detail, instead less attention has been focused on the role of the common solvent. Poly(ethylene oxide)- block -poly(lactic acid) (PEO- b -PLA) is widely used for the preparation of nanometric drug delivery systems and the control of the particle morphology has relevant effects on bioactivity. In this work we investigate the effect of using different common solvents (acetone, dioxane, tetrahydrofuran, dimethylformamide) on the self-assembly behavior of narrowly dispersed PEO- b -PLA copolymers, synthesized by metal free ring-opening polymerization, with large variation of molecular weight of the hydrophobic block (from 65 to 1300 lactic units). Dynamic light scattering (DLS) and cryo-electron microscopy (cryo-EM) analyses of PEO- b -PLA nanoparticles reveal that their size and shape are strongly dependent on the hydrogen bonding ability of the common solvent used in the self-assembly process. As consequence of these variations, also the cytoxicity of the nanoparticles is affected. Graphical abstract: Image 1 Highlights: A library of PEO- b -PLA copolymers has been synthesized by DBU catalyzed ROP. The self-assembly of PEO- b -PLA copolymers has been realized in a variety of common solvents. The hydrogen bonding ability of the solvent has a relevant effect on the self-assembly.